Understanding the Function of Emojis in TikTok Comments for Prabowo Subianto - Nikita Isabel Prasetya (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study examined the use of emoji in TikTok comments about Prabowo Subianto from the first presidential debate. This study applied Yus’ (2014) framework which identifies eight distinct emoji functions. Conducted through a qualitative analysis of 50 comments collected on the day of the video’s release, the findings indicated that emoji used performed all functions except for the illocutionary force modifier. The emoji used suggest vibrant and expressive interactions, where the TikTok users reacted both light-heartedly and critically. The absence of illocutionary force modifiers aligns with Prabowo Subianto's direct communication style, which prompts more straightforward responses from the TikTok users.